SISTEM PENUNJANG KEPUTUSAN UNTUK MENENTUKAN UKURAN OUTWEAR OTOMOTIF TOKO RON'S STORE MENGGUNAKAN METODE NAIVE BAYES - Bryan Riyanto; Jap Tji Beng; Dedi Trisnawarman (Fakultas Teknologi Informasi Universitas Tarumanagara, 2019)
The purpose of this research is to develop a decision support system to help determine the size of the outwear motorcycles in Ron's Store. The methods used in the writing of this thesis is the Naïve Bayes. The result is an application can perform the calculation to find the greatest probability that it can figure out a more appropriate size, applications running with XAMPP as Localhost and PHPMyadmin as the database. Based on the test results it can be concluded that the system can assist the customer in determining the size of the product which is more appropriate.